“Death drive” scientifically reconsidered: Not a drive but a collection of trauma-induced auto-addictive diseases - Kirsch, Michael; Dimitrijevic, Aleksandar; Buchholz, Michael B. (Frontiers in Psychology, 2022)
Over the last 102 years, a lot of discussion was being held about the psychoanalytic conception of the “death drive,” but still with inconclusive results. In this paper, we start with a brief review of Freud’s conception, followed by a comprised overview of its subsequent support or criticisms. The core of our argument is a systematic review of current biochemical research about two proposed manifestations of the “death drive,” which could hopefully move the discussion to the realm of science. It was already established that drive satisfaction leads to the secretion of beta-endorphins, and research evidence also shows that the same biochemical mechanisms get activated in the case of masochism and the gambling disorder but only if they are preceded by chronic frustration of the essential drives. We conclude that the actual situation is more complex than Freud hypothesized, and that a fundamental revision of the psychoanalytic drive theory is necessary.